Giant Orbitoethmoidal Osteoma: When an Open Surgical Approach Is Required - Hussam Abou Al-Shaar; Turki El Arjani; Michael S. Timms; Faisal Al-Otaibi (Case Reports in Otolaryngology)
Giant orbitoethmoidal osteoma in children is considered to be rare. This type of pathology can be associated with significant disfiguring proptosis and limitation of eye movement. Here, we report on a child who presented with a giant orbitoethmoidal osteoma that was removed through an orbitofrontal approach. The cosmetic result was excellent and evident immediately after surgery. A review of the literature complements this report.